1974
DOI: 10.2134/jeq1974.00472425000300040025x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Removal from Floodwater Overlying Flooded Soils and Sediments

Abstract: The floodwater NO3− removal rate of intermittently‐flooded fresh water swamp soils and continuously‐flooded saline marsh soils of southern Louisiana was quantitatively characterized in a laboratory study. Of the two areas studied, the marsh area was the more effective sink for NO3− contaminated waters with an average initial removal rate of 9.15 ppm N/day. After correcting for the rate of NO3− diffusion, the microbial NO3− removal rate was calculated to be 7.64 ppm N/day. The swamp soil had a removal rate of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(28 citation statements)
references
References 0 publications
1
27
0
Order By: Relevance
“…Nitrate uptake by aquatic plants, NO 3-reduction, and denitrification in the water and underlying anaerobic soil probably accounted for NO s-removal from the inflow drainage water. Several studies (Engler and Patrick 1974, Reddy and others 1978, 1980 have indicated that NOsremoval from the overlying floodwater was due to diffusion of NOs-into underlying soil followed by denitrification. In the reservoirs, NOs ~ removal by reservoir R1, or reservoir R2 (first reservoir in series of small reservoirs) was probably due to assimilation by waterhyacinth plants (Dunigan andothers 1975, Cornwell andothers 1977) and to denitrification in the anaerobic water column and underlying sediments.…”
Section: Associated Processesmentioning
confidence: 98%
“…Nitrate uptake by aquatic plants, NO 3-reduction, and denitrification in the water and underlying anaerobic soil probably accounted for NO s-removal from the inflow drainage water. Several studies (Engler and Patrick 1974, Reddy and others 1978, 1980 have indicated that NOsremoval from the overlying floodwater was due to diffusion of NOs-into underlying soil followed by denitrification. In the reservoirs, NOs ~ removal by reservoir R1, or reservoir R2 (first reservoir in series of small reservoirs) was probably due to assimilation by waterhyacinth plants (Dunigan andothers 1975, Cornwell andothers 1977) and to denitrification in the anaerobic water column and underlying sediments.…”
Section: Associated Processesmentioning
confidence: 98%
“…It is the coupling of aerobic (nitrification) and anaerobic (denitrification) reactions that allows wetlands to function most effectively to "remove" nitrogen from the ecosystem. In contrast to deeper aquatic systems, the shallow water-sediment interface (Engler and Patrick 1974), root rhizospheres (Reddy, Patrick, and Lindau 1989), and alternating dry and inundated conditions of wetlands favor nitrification-denitrification reactions (Ponnamperuma 1972). This is the reason that the conversion of shallow, more seasonal type wetlands to deeper, more permanent type wetlands actually decreases many of the microbially mediated biogeochemical functions.…”
Section: Function 4: Remove Convert and Sequester Dissolved Substancesmentioning
confidence: 99%
“…Generally, nitrification may not be completely inhibited in wet or flooded rice soils because NH4 could be oxidized to NO3 in the thin O2-containing surface soil layer and in the overlaying water phase of flooded soils [35]. Although nitrifying activity in flooded soils may be substantially lower than in unflooded soils, a large number of nitrifying organisms have been shown to occur in the surface layers of flooded soils [33]; the number, however, decreased with soil depth.…”
Section: Nitrificationmentioning
confidence: 99%